DAMPAK PENGGUNAAN KATA-KATA PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN - Santi Kharismawati; Nadila Monika; Heru Pratikno (Jurnal Bina Bangsa Ekonomika, 2024)
In the realm of marketing, promotional efforts have a crucial role in shaping consumer purchasing decisions. This research focuses on exploring the concrete impact of the use of promotional words on consumer purchasing decisions. Using a quantitative approach, we collected data from randomly selected respondents through carefully designed questionnaires. Statistical analysis was used to identify the relationship and significance of the influence of promotional words on consumer purchasing decisions. The results of this study are expected to provide deeper insights, enriching marketing practitioners' understanding of how promotional elements, especially words, can directly influence consumer purchasing decisions. The practical implications of these findings are expected to be a valuable guide in designing more targeted and effective promotional strategies